2022
DOI: 10.51847/osvixvsolx
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiological study of the use of e-pharmacies by the population

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Counterfeit drugs pose serious threats to the public since they could have no effect, produce a negative effect or lead to detrimental ramifications on the patient’s medical condition. Additional concerns include receiving incorrect information about drugs31 and numerous order rejections 32…”
Section: Discussionmentioning
confidence: 99%
“…Counterfeit drugs pose serious threats to the public since they could have no effect, produce a negative effect or lead to detrimental ramifications on the patient’s medical condition. Additional concerns include receiving incorrect information about drugs31 and numerous order rejections 32…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed a link between using online pharmacies and the following sociodemographic factors: a higher level of education, advanced age, higher family income, greater number of prescriptions and/or marital status ( Atkinson et al, 2009 ; Brown and Li, 2014 ; Fittler et al, 2018 ; Jairoun et al, 2021 ). During the past 2 years, only a relatively small number of national ( Bowman et al, 2020 ; Cherecheș and Popa, 2021 ; Jairoun et al, 2021 ; Sun et al, 2021 ; Soboleva et al, 2022 ) surveys have been conducted, thus, there is little data measuring the effects of the coronavirus epidemic on the prevalence of online purchases and the attitude changes towards internet pharmacies. Evidently, COVID-19 has accelerated trends which were already growing; however, it is debatable if the changes in internet pharmacy utilization will outlast the pandemic.…”
Section: Introductionmentioning
confidence: 99%